2009
DOI: 10.1029/2008gl035815
|View full text |Cite
|
Sign up to set email alerts
|

Warm ocean anomaly, air sea fluxes, and the rapid intensification of tropical cyclone Nargis (2008)

Abstract: On 2 May 2008, category‐4 tropical cyclone Nargis devastated Myanmar. It was observed that just prior to its landfall, Nargis rapidly intensified from a weak category‐1 storm to an intense category‐4 storm within only 24 h. Using in situ ocean depth‐temperature measurements and satellite altimetry, it is found that Nargis' rapid intensification took place on a pre‐existing warm ocean anomaly in the Bay of Bengal. In the anomaly, the subsurface ocean is evidently warmer than climatology, as characterized by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
178
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 228 publications
(190 citation statements)
references
References 17 publications
4
178
0
Order By: Relevance
“…Recent investigations indicate that warm core eddies favour the enhancement of typhoons, because the eddies have a large upper ocean heat content (UOHC) (Lin et al, 2009;Wu, Lee, & Lin, 2007). It has been found that the relatively warmer upper ocean, characterized by a large D26 (depth of the 26°C isotherm), leads to a reduction in cyclone-induced ocean cooling (Lin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent investigations indicate that warm core eddies favour the enhancement of typhoons, because the eddies have a large upper ocean heat content (UOHC) (Lin et al, 2009;Wu, Lee, & Lin, 2007). It has been found that the relatively warmer upper ocean, characterized by a large D26 (depth of the 26°C isotherm), leads to a reduction in cyclone-induced ocean cooling (Lin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the relatively warmer upper ocean, characterized by a large D26 (depth of the 26°C isotherm), leads to a reduction in cyclone-induced ocean cooling (Lin et al, 2009). For a slow-moving Category 5 typhoon (maximum sustained winds higher than 61 m s , respectively (Lin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest recorded storm surge (*12.5 m) was associated with the Backergunj cyclone that was originated in BoB in 1876 and struck near Meghna estuary in Bangladesh. In the historical cyclone records, seven of the top ten deadliest cyclones have formed in the BoB and the most recent example is cyclone Nargis (May 2008) in Myanmar (Webster 2008;Lin et al 2009;McPhaden et al 2009;Yanase et al 2010). TC Sidr (November 2007) which was a Category 4 storm in SaffirSimpson Tropical Cyclone Scale (SSTCS) brought about a devastating coastal flooding with *5.8 m of surge height and *1.7 billion (USD) of damage in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%